A Comparison of the Effects of Skin-to-Skin Contact Versus Conventional Method on Newborn Body Temperature - Bukhari, Yusra; Khan, Shazia Majid; Amjad, Sumbal (Biological and Clinical Sciences Research Journal, 2025)
Neonatal thermal protection remains a significant global issue and a challenge for medical professionals. Maintaining the newborn in a natural thermal environment is essential by keeping them on their mother's belly for as long as possible. Objective: The current study aimed to compare the change in newborns mean body temperature after skin-to-skin contact and conventional Method: Materials and method: The current randomised control trial study was carried out at the gynecology and Obstetrics department Sheikh Zayed Hospital and college Rahim Yar Khan over three months from December 16, 2024 to March 16, 2025 after taking permission from the ethical board of the institute. Non-probability consecutive sampling was employed, and the sample size was calculated using the WHO sample size calculator. The sample consisted of 120 participants, divided into two groups of 60 each. Using the lottery approach, the mothers were split into two groups: Group B (skin-to-skin contact) and Group A (baby warmer group). In Group A, the newborns were dried and covered with a warm towel within ten minutes of birth. The infant was kept in a radiant warmer for at least an hour. In Group B, within 10 minutes after birth, the newborns were placed on the mother's chest, preserving skin-to-skin contact. Using a digital thermometer, the principal investigator used data collection procedures to monitor the newborn's axillary body temperature at 15, 30, and 60 minutes after birth. SPSS version 26.0 was used to analyse the data. A p-value of ≤ 0.05 was considered statistically significant. Results: Compared to the A group, participants in the B group were younger. In both groups, the most prevalent age group was 25 to 31 years. The average length of stay in the hospital was 6.5 ± 1.5 hours. The average length of hospital stay using the conventional method was 6.5 ± 1.5 hours, while the average length of skin-to-skin mother contact was 6.7 ± 1.8 hours. Patients' health responses were determined to be 15 (25%) in the Conventional Approach group and 36 (60%) in the Skin-to-Skin Mother-Contact group. After 60 minutes, a statistically significant mean temperature difference was observed between the two groups (p = 0.001); however, no significant mean temperature difference was found after 30 or 15 minutes (p > 0.05). Conclusion: The current study concluded that Skin-to-skin contact should be encouraged and maintained, as it helps lower the risk of hypothermia. It is inexpensive, simple, and promotes bonding between mothers and children.